CD30-Positive Extracellular Vesicles Enable the Targeting of CD30-Negative DLBCL Cells by the CD30 Antibody-Drug Conjugate Brentuximab Vedotin - Lobastova, Liudmila; Lettau, Marcus; Babatz, Felix; de Oliveira, Thais Dolzany; Nguyen, Phuong-Hien; Pauletti, Bianca Alves; Schauss, Astrid C.; Dürkop, Horst; Janssen, Ottmar; Paes Leme, Adriana F.; Hallek, Michael; Hansen, Hinrich P. (Frontiers in Cell and Developmental Biology, 2021)
CD30, a member of the TNF receptor superfamily, is selectively expressed on a subset of activated lymphocytes and on malignant cells of certain lymphomas, such as classical Hodgkin Lymphoma (cHL), where it activates critical bystander cells in the tumor microenvironment. Therefore, it is not surprising that the CD30 antibody-drug conjugate Brentuximab Vedotin (BV) represents a powerful, FDA-approved treatment option for CD30+ hematological malignancies. However, BV also exerts a strong anti-cancer efficacy in many cases of diffuse large B cell lymphoma (DLBCL) with poor CD30 expression, even when lacking detectable CD30+ tumor cells. The mechanism remains enigmatic. Because CD30 is released on extracellular vesicles (EVs) from both, malignant and activated lymphocytes, we studied whether EV-associated CD30 might end up in CD30- tumor cells to provide binding sites for BV. Notably, CD30+ EVs bind to various DLBCL cell lines as well as to the FITC-labeled variant of the antibody-drug conjugate BV, thus potentially conferring the BV binding also to CD30- cells. Confocal microscopy and imaging cytometry studies revealed that BV binding and uptake depend on CD30+ EVs. Since BV is only toxic towards CD30- DLBCL cells when CD30+ EVs support its uptake, we conclude that EVs not only communicate within the tumor microenvironment but also influence cancer treatment. Ultimately, the CD30-based BV not only targets CD30+ tumor cell but also CD30- DLBCL cells in the presence of CD30+ EVs. Our study thus provides a feasible explanation for the clinical impact of BV in CD30- DLBCL and warrants confirming studies in animal models.